2017
DOI: 10.1155/2017/6713606
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of miR-29b-3p in Arterial Calcification by Targeting Matrix Metalloproteinase-2

Abstract: Vascular calcification is a risk predictor and common pathological change in cardiovascular diseases that are associated with elastin degradation and phenotypic transformation of vascular smooth muscle cells via gelatinase matrix metalloproteinase-2 (MMP2). However, the mechanisms involved in this process remain unclear. In this study, we investigated the relationships between miR-29b-3p and MMP2, to confirm miR-29b-3p-mediated MMP2 expression at the posttranscriptional level in arterial calcification. In male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Furthermore, MMP2 is a known target of the miR-29 family, members of which directly inhibit MMP2 expression and suppress cancer cell adhesion, invasion and metastasis [17][18][19][20]. We recently reported that miR-29b-3p regulates MMP2 expression in VC in rats and confirmed MMP2 as a target gene of miR-29b-3p [21]. Therefore, herein we test whether miR-29b-p regulates transdifferentiation and calcification of VSMCs in a calcified environment by affecting MMP2 expression in vitro.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, MMP2 is a known target of the miR-29 family, members of which directly inhibit MMP2 expression and suppress cancer cell adhesion, invasion and metastasis [17][18][19][20]. We recently reported that miR-29b-3p regulates MMP2 expression in VC in rats and confirmed MMP2 as a target gene of miR-29b-3p [21]. Therefore, herein we test whether miR-29b-p regulates transdifferentiation and calcification of VSMCs in a calcified environment by affecting MMP2 expression in vitro.…”
Section: Introductionmentioning
confidence: 90%
“…Among them, 15 (40.5%) have been confirmed or are suspected to promote or aggravate VC in different scenarios, while 22 (59.5%) protect against VC formation or progression. Direct gene targets have been identified for 14 miRNAs with negative VC regulatory capacity, including miR-29a/29b [14], miR-29b-3p [34], miR-30b [16,47], miR-30c [16], miR-30e [25], miR-34b/34c [29,64], miR-125b [13,22] miR-133a [19], miR-135a [30], miR-182 [42], miR-204 [15,41,50], and miR-205 [21], while few direct targets have been identified for miRNAs with VC enhancement ability (miR-34a [39], miR-128-3p [48], and miR-135a-3p [17]). In the following sections, we describe the clinical features of each VC-regulating miRNA based on their propensity for positive or negative vascular influences.…”
Section: Mirnas In Vc: Positive and Negative Vc Regulatorsmentioning
confidence: 99%
“…The MiR-29 family contain three members, namely miR-29a, 29b, and 29c; these members exhibit immunoregulatory ability, affect muscle cell physiology, and modulate cell survival [98]. Experiments based on rat, human VSMCs, and calcified arteries from rat showed that miR-29a/29b/29c could ameliorate [14,34,44] or aggravate [26,32] calcification progression (Table 1). We believe that this controversial finding can be interpreted from the following perspective; first, those with the direct targets of miR-29 family members uncovered [14,34] all concluded that these miRNAs were negative VC regulators.…”
Section: Mirnas With Controversial Influences On Vcmentioning
confidence: 99%
See 2 more Smart Citations